(untitled) (Journal of the College of Basic Education, 2023)
The export threshold threshold is an intermediate (association) between the author region and the text region; in order to initializeThe position to move and cross over to the reader’s area», as the writer borrows a water saying, a poet’s verse, or a famous ideaFor a philosopher, thinker, writer, poet, etc., or with a statement of his that confirms his personal presence betweenThe constellation of thinkers, writers, and philosophers whose sayings he borrows in order to be guided by them intellectually and semantically; And he insists on itHis literary discourse, putting this borrowed saying on the first page with the title grape or on the page thatfollowed remarkably; This threshold may precede the title of complete poetic works or a collection of poetryone; or a particular poem. There is no doubt that the effectiveness of the focus that we enjoy as an export grape in this way is interfering in a way What is in the space of the concentrated poem that characterizes the poem of the poet Abd al-Razzaq al-Rubaie? You work on focusMeaning, significance and value in a very economical and limited written space. So that suggests great interestThe widespread use of this threshold is a kind of revealing of the poet’s concentrated poem, as the awareness ofThe focus and its privacy appear prominently in this event, which is consistent, parallel and consistent with natureThe concentrated poem and its privacy.